Pharmacological Treatment of Presbyopia Using Pilocarpine 1.25% Eye Drops - Seyed Abolghasem Mousavi; Zhale Rajavi; Hamideh Sabbaghi; Saeid Abdi; Nafeeseh Montazerin; Bahareh Kheiri; Azadeh Haseli- Monfared; Kourosh Sheibani; Hemn Baghban Jaldian (Journal of Ophthalmic & Vision Research)
Purpose: To assess the efficiency and safety of pilocarpine eye drop 1.25% analogue (IRPilo) in comparison with its original brand-name drug (Vuity). Methods: In this non-randomized comparative study, 75 patients with presbyopia aged 40 to 60 years were enrolled. The right eyes of these patients received either IR-Pilo (n = 45) or Vuity (n = 30) and their contralateral eyes served as controls. Refractive errors, distance best-corrected visual acuity (BCVA), near vision, amplitude of accommodation, pupil size, and intraocular pressure (IOP) were measured before and 1 to 2 hours after instillation of the eye drop. Results: The mean refractive error was stable, except for a small myopic shift in the Vuity group. There was no significant change in distance BCVA. Near vision improved significantly in both intervention groups (P < 0.001) with preference for IR-Pilo (4 vs 2.3). Furthermore, a higher amplitude of accommodation and pupil constriction occurred after instillation of both drops, with a higher effect associated with IR-Pilo. However, IOP did not change significantly post intervention. Conclusion: IR-Pilo and Vuity eye drops had comparable results; both were effective and led to stable distance vision and improved near vision. Both ophthalmic drugs were safe and none of them were associated with significant adverse effects.